Leitbild nachhaltige Entwicklung - Konsequenzen für die Gesellschaftstheorie. Forschungsdesiderate und Vorschlag einer sozialgeographischen Forschungsprogrammatik - Zierhofer, Wolfgang (ERDKUNDE, 2007)
According to the mainstream of modern social sciences, nature and environment are opposed to the social and not regarded as part of the disciplinary object field. This view is profoundly challenged by the regulative idea of sustainable development, since it urges reconciliation of ecological, economic and social demands. This paper discusses the state of the art of integrating nature, environment or the biophysical world into the basics of social theory. It shows further that so far the relations between society and environment have so far not been sufficiently conceptualized on the level of collective or aggregated interactions, and thus the macro-level of social theory. In respect of this research desideratum, the paper presents a research strategy, which sets out from the concept of “ecological regimes”.